Convergence of lemniscal and local excitatory inputs on large GABAergic tectothalamic neurons. Issue 15 (12th May 2015) - Ito, Tetsufumi; Hioki, Hiroyuki; Sohn, Jaerin; Okamoto, Shinichiro; Kaneko, Takeshi; Iino, Satoshi; Oliver, Douglas L.
ABSTRACT Large GABAergic (LG) neurons form a distinct cell type in the inferior colliculus (IC), identified by the presence of dense VGLUT2‐containing axosomatic terminals. Although some of the axosomatic terminals originate from local and commissural IC neurons, it has been unclear whether LG neurons also receive axosomatic inputs from the lower auditory brainstem nuclei, i.e., cochlear nuclei (CN), superior olivary complex (SOC), and nuclei of the lateral lemniscus (NLL). In this study we injected recombinant viral tracers that force infected cells to express GFP in a Golgi‐like manner into the lower auditory brainstem nuclei to determine whether these nuclei directly innervate LG cell somata. Labeled axons from CN, SOC, and NLL terminated as excitatory axosomatic endings, identified by colabeling of GFP and VGLUT2, on single LG neurons in the IC. Each excitatory axon made only a few axosomatic contacts on each LG neuron. Inputs to a single LG cell are unlikely to be from a single brainstem nucleus, since lesions of individual nuclei failed to eliminate most VGLUT2‐positive terminals on the LG neurons. The estimated number of inputs on a single LG cell body was almost proportional to the surface area of the cell body. Double injections of different viruses into IC and a brainstem nucleus showed that LG neurons received inputs from both. These results demonstrated that both ascending and intrinsic sources converge on the LG somata to control inhibitory tectothalamic projections. J. Comp. Neurol. 523:2277–2296, 2015. © 2015 Wiley Periodicals, Inc.